Theoretical and Practical Principles of Primary Education in Vasyl Sukhomlynsky’s Legacy - Sevastiuk, Mariana; Perepeliuk, Inna; Hubarieva, Daria (My University, 2021)
The article attempts to analyze the main ideas of Vasyl Sukhomlynsky’s educational work concerning the purpose, content and specific features of the organization of primary education in the Pavlysh School. Being aware of the significant role of primary education in the overall development of a child and the great experience of Sukhomlynsky in improving the quality of primary education, it is thus necessary to rethink his ideas in accordance with the new requirements of modern education. First of all, the purpose and tasks of primary education have been analyzed in accordance with Sukhomlynsky’s requirements. The views of the prominent educator on the importance of developing universal values, general learning skills and assimilation of basic knowledge which is necessary for successful further learning by younger schoolchildren have been outlined. The influence of the leading ideas of Sukhomlynsky – humane pedagogy, child-centrism and human studies – on the development of basic organizational principles of teaching in primary school has been determined. Sukhomlynsky’s ideas regarding the introduction of a diagnostic approach to conducting classes, confident achievement of positive learning results in the «school of joy», which was created by the educator, can significantly improve the quality of primary education. The influence of Sukhomlynsky’s ideas concerning the creation of learning environment of the educational institution, integration of school subjects through the introduction of outdoors lessons of thinking, and new approaches to the evaluation of educational achievements of younger students, on the quality of modern primary education have been characterized. The innovative teaching methods and techniques that were used by the teacher in the educational process of the Pavlysh School have been considered and can be effectively applied by primary school teachers. The article also proves that Sukhomlynsky’s ideas were way ahead of their time, and that the Ukrainian school reforming process is based on the best traditions of national pedagogy and education
Keywords: humanism, child-centrism, competency-based approach, general learning skills, educational environment, health-saving function of education, education content integration, innovative teaching methods.